Kualitas Pelayanan Publik Pada PLN Mobile - Marlina Isna Nur Aulia; Muhammad Dzikri Mustopa; Mutiara Zulfa (Gunung Djati Conference Series, 2024)
Technological advances provide benefits in public services to the community, especially at PT. PLN (Persero). Utilization of technology with good quality can provide satisfaction for the community itself. This research is entitled "Improving the Quality of PLN Public Services Through the Use of Technology to Create Community Satisfaction". This research aims to determine public satisfaction in improving the quality of public services. The approach methodology uses quantitative methods with techniques for analyzing substances and scraping data from various internet sources. The diagram shows that 10,000 PLN Mobile 8000 users gave a 5star rating, 1000 users gave a 1 star, 500 users gave a 4 star, and 200 users gave a 2 star, and there were no 3 stars. By increasing the efficiency and quality of public services using PLN Mobile, it is easier for people to access information related to electricity services. This can also increase PLN's transparency, accountability and sense of responsibility to the community.